Основні проблеми зовнішньоекономічної діяльності підприємств України: стаття - Черчик, Лариса Миколаївна; Cherchyk, Larysa M.; Cherchyk, Larysa M. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті розглянуто основні проблеми зовнішньоекономічної діяльності підприємств України, визначено динаміку, регіональну, товарну структуру експорту та імпорту; виявлено чинники впливу на зовнішньоекономічну діяльність; узагальнено та згруповано проблеми їх розвитку. In the article the basic problems of foreign economic activity of enterprises in Ukraine. The dynamics of exports and imports of goods identified regional and commodity structure of exports and imports, trends and characteristics. Past studies have identified group level and negative factors influence the development of foreign economic activity of enterprises: external (macro-factors of the global environment, financial, economic, institutional, political), direct (intermediate environment - geopolitical, legal and regulatory, regulatory, financial economic); internal (micro- technical, technological, financial, management, staffing). Overview and grouped problems of development and improvement directions of foreign economic activity of enterprises in Ukraine.
The Main Problems of Ukraine International Business
Keywords: експорт; зовнішньоекономіча діяльність; імпорт; підприємства; управління; розвиток; enterprise; foreign economic activity; export; import; balance; management; development